Nanostructure-induced performance degradation of WO3·nH2O for energy conversion and storage devices - Hai, Zhenyin; Karbalaei Akbari, Mohammad; Wei, Zihan; Cui, Danfeng; Xue, Chenyang; Xu, Hongyan; Heynderickx, Philippe M.; Verpoort, Francis; Zhuiykov, Serge (Beilstein Journal of Nanotechnology, 2018)
Although 2D layered nanomaterials have been intensively investigated towards their application in energy conversion and storage devices, their disadvantages have rarely been explored so far especially compared to their 3D counterparts. Herein, WO3·nH2O (n = 0, 1, 2), as the most common and important electrochemical and electrochromic active nanomaterial, is synthesized in 3D and 2D structures through a facile hydrothermal method, and the disadvantages of the corresponding 2D structures are examined. The weakness of 2D WO3·nH2O originates from its layered structure. X-ray diffraction and scanning electron microscopy analyses of as-grown WO3·nH2O samples suggest a structural transition from 2D to 3D upon temperature increase. 2D WO3·nH2O easily generates structural instabilities by 2D intercalation, resulting in a faster performance degradation, due to its weak interlayer van der Waals forces, even though it outranks the 3D network structure in terms of improved electronic properties. The structural transformation of 2D layered WO3·nH2O into 3D nanostructures is observed via ex situ Raman measurements under electrochemical cycling experiments. The proposed degradation mechanism is confirmed by the morphology changes. The work provides strong evidence for and in-depth understanding of the weakness of 2D layered nanomaterials and paves the way for further interlayer reinforcement, especially for 2D layered transition metal oxides.
Keywords: 2D layered oxides; interlayer water; van der Waals interaction; WO3·nH2O